(untitled) (Bulletin KNOB, 2005)
In Dutch history of architecture the first half of the eighteenth century is sometimes defined as the ’era without architects’. Prominent architects and building contractors from the second half of the seventeenth century lacked worthy successors, large commissions were not forthcoming and even the wealthiest private individuals put up with ’carpenter’s designs’. Work bosses, the heads of large building companies who worked with fixed workshops of craftsmen and artists, dominated the building production and acted as designers together with painters and sculptors. Apart from them, there were free designers, who did not work in the building trade and were not members of a guild, but who had acquired a position by means of their draughtsmanship. Because of the lack of great ’building artists’ the entire period is considered rather unspectacular from an art-historical point of view, the only bright spots being the work of a few artist-architects. In this picture of architectonic culture the role of the commissioner as definer, designer and supervisor, in brief, as architect in the contemporary sense of the word, remained almost unnoticed, whereas the role of the craftsman or work boss was reduced to that of executor of the designs of others. At best, these trendsetters were portrayed as dilettantes, exceptions in a building trade dominated by artists and building contractors. In this article an attempt is made to reconstruct the crucial role of the commissioner in early-modern architectonic culture. The publications that appeared on architecture, the so-called ’architecture in writing’, were chiefly aimed at the large group of amateurs. By means of historiographical attention, the reasons are also examined why this commissioner was recorded in such a fragmentary way in the history of architecture and the craftsman reduced to a pragmatist utterly lacking in higher theoretical insight. The roots of this view seem to lie in the nineteenth-century emancipation of the ’building artist’. At that time the concept of ’amateur’ acquired a disparaging meaning, and the status of the craftsman/pragmatist declined to such an extent that both were no longer regarded as architects, but as ’unqualified’ persons.